The second “Pablo Hasél case” - Dopico Gómez-Aller, Jacobo (EUNOMÍA. Revista en Cultura de la Legalidad, 2021)
The second conviction of the musician Pablo Hasél for offences related to acts of expression (insulting members of the royal family, glorifying terrorism and insulting the police) has generated significant controversy. This text proposes a detailed analysis of the expressions that led to the conviction, and compares the reasoning of the convictions with the standards of the Constitutional Court and the European Court of Human Rights on freedom of expression.
Keywords: freedom of expression; insult to the crown; glorification of terrorism; insult to the police; European Court of Human Rights